Migration and development : pro-poor policy choices - Siddiqui, Tasneem (University Press, 2005)
Contributed articles presented at an international conference organized by DFID and Refugee amd Migratory Movements Research Unit, University of Dhaka with reference to emigration and immigration in various South Asian countries for economic reasons.